Analisis Steganography Terhadap Keamanan Data - Juman, Kundang Karsono (Lembaga Penerbitan Universitas Esa Unggul, 2008)
The computer security system includes security data this time able to issue demand. Steganography is the art of concealing the existence of information within seemingly innocuous carriers. Steganography can be viewed as akin to cryptography. Both have been used throughout recorded history as means to protect information. At times these two technologies seem to converge while the objectives of the two differ. Cryptographic techniques